Atlas of lymph node pathology - Nathwani, Bharat N., 1945-; Hansmann, Martin (New York : Chapman & Hall, 1997)
Covers 77 disease entities and 143 diagnostic features, with accompanying descriptions. Information can be accessed by disease and by feature. Lectures and references are also available
disc 1. Reactive -- disc 2. Non-Hodgkin's -- disc 3. Metastic & misc
Title from disc label
System requirements: IBM PC (486SX or higher) or compatible; 8MB RAM, 5MB hard drive space; Windows 3.1 or higher; CD-ROM drive, SVGA, mouse
System requirements: Macintosh; 8MB RAM, 5MB hard drive space; CD-ROM drive, SVGA, mouse
Keywords: Lymph Nodes -- pathology -- atlases; Lymphatic Diseases -- pathology -- atlases